2021
DOI: 10.15244/pjoes/130988
|View full text |Cite
|
Sign up to set email alerts
|

Surface Water Quality in the Mantaro River Watershed Assessed after the Cessation of Anthropogenic Activities Due to the COVID-19 Pandemic

Abstract: In late December 2019, the emerging disease COVID-19 was identified as a global pandemic. Countries around the world have implemented various types of blockades to stop this infection. These health measures have led to a significant reduction in air pollution. However, the impact of these measures on aquatic environments has been little analyzed. In this context, the water quality of rivers in the Mantaro River basin was evaluated using multivariate statistical methods and heavy metal contamination indices dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 36 publications
0
8
0
2
Order By: Relevance
“…The transfer factor (TF) result reflects the potential ability of PTE to move from soil to edible parts of artichoke from sectors irrigated by PTE contaminated water (Table S2) ( Custodio et al, 2021 ). The transfer of PTE from soil to food crops is one of the key processes through which humans are exposed ( Kumar et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The transfer factor (TF) result reflects the potential ability of PTE to move from soil to edible parts of artichoke from sectors irrigated by PTE contaminated water (Table S2) ( Custodio et al, 2021 ). The transfer of PTE from soil to food crops is one of the key processes through which humans are exposed ( Kumar et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Soil contamination through irrigation with PTE contaminated water leads to cross-contamination of food. In the Mantaro River basin in the central region of Peru, large extensions of agricultural soils are irrigated with PTE contaminated water for more than eight decades ( Custodio et al, 2021 ). The continuous use of these waters for irrigation has led to the accumulation of PTE in the agricultural soils of the study area, as revealed by our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Improved water quality of rivers due to Covid-19 lockdown was observed from other parts of the world as well such as Turkey (Tokatli and Varol 2021 ), China (Liu et al 2021 ), Malaysia (Najah et al 2021 ) and Peru (Custodio et al 2021 ).…”
Section: Covid-19 and Hydrospherementioning
confidence: 93%
“…Estos datos indican contaminación de ambos recursos. A largo plazo, alta concentración de Cd en el agua de riego del río Mantaro incrementará la cantidad de Cd absorbido por Alcachofa (Custodio et al, 2020;MINAM, 2019). La presencia de Cd en cultivos como la alcachofa causa un incremento potencial en la cantidad absorbida por humanos y animales, pues son alimentos de consumo cotidiano, que se incorporan a la cadena alimenticia, y se acumulan en los organismos (Antoniadis et al, 2019).…”
Section: Concentración De Cadmiounclassified
“…El Perú, caracterizado por su déficit de agua para la producción agrícola, tiene áreas irrigadas con agua contaminada por elementos potencialmente tóxicos que a largo plazo favorecen la absorción por los cultivos alimenticios (Custodio et al, 2020). El cultivo de alcachofa (Cynara scolymus L.), utilizado para la alimentación, por su alta calidad nutritiva, en la provincia de Concepción, departamento de Junín, utiliza las aguas del río Mantaro para irrigar los campos de cultivo, como en los distritos como Huaychulo y Mito, debido a las condiciones favorables de clima para su desarrollo.…”
Section: Introductionunclassified